Ballistic impact experiments of titanium-based carbon-fibre/epoxy laminates. (October 2022) - Sun, Jing; Xu, Shanqing; Lu, Guoxing; Wang, Qing; Gong, Ao
Abstract: In this paper, high-velocity impact resistance of lightweight laminates with multi-layers of carbon-fibre/epoxy laminates sandwiched by two titanium alloy skins and aluminium alloy skins was extensively investigated by experiments with a total of 48 impact tests conducted. The ballistic limit of the titanium-based carbon-fibre/epoxy laminate was estimated to be between 241.6 m/s and 257.1 m/s. Impact velocity governed energy absorption and the corresponding damage modes were characterised and identified. The influence of fibre metal laminates configuration on the impact resistance was then experimentally investigated at a fixed impact velocity with full penetration in ten types of laminates. The results also showed that thicker skin and higher number of fibre layers favoured the specific energy absorption in the tested matrix. Highlights: The estimated ballistic limit velocity V 50 for TI-CF FMLs is between 241.6 and 257.1 m/s. The failure mechanisms of TI-CF FMLs are categorised into four modes. Thicker skin and higher number of fibre layers favoured high specific energy absorption.